2017
DOI: 10.24248/eahrj-d-16-00364
|View full text |Cite
|
Sign up to set email alerts
|

Beyond the Numbers: Interpreting WHO's Global Tuberculosis Report 2016 to Inform TB Policy and Practice in the East African Community

Abstract: By 2000, 5 East African Community (EAC) member states-Uganda, Kenya, Tanzania, Rwanda, and Burundi-had adopted the World Health Organization's (WHO's) policy of directly observed treatment short-course (DOTS) for tuberculosis (TB). This policy is meant to speed up the control of TB through effective diagnosis and treatment. However, the rate of reduction of TB burden has been slow, and as of 2016, 3 EAC member states-Uganda, Kenya, and Tanzania-are still categorised as high TB burden countries. We analysed WHO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…Even when Mozambique achieves the required capacity of six culture laboratories, samples will need to be transported over a distance of >20 000 km 2 and at high ambient temperatures [ 5 ]. The situation is not different in many other resource-limited high-burden TB countries [ 21 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Even when Mozambique achieves the required capacity of six culture laboratories, samples will need to be transported over a distance of >20 000 km 2 and at high ambient temperatures [ 5 ]. The situation is not different in many other resource-limited high-burden TB countries [ 21 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Tuberculosis (TB) has prevailed for millennia and remains a major health problem worldwide ( Sabiiti and consortium, 2017 ). Increasing incidences of multidrug resistant cases of TB are a major threat.…”
Section: Molecular Docking Simulation Of Amentoflavone Through In Silico Approachmentioning
confidence: 99%
“…Consequently, there is an urgent need to necessitate culturally sensitive health education on TB disease targeting men to clarify any myths and misperceptions and enhance positive attitudes towards TB disclosure. Poverty is the second reported determinant that hampers TB treatment and care 45 70. This study has shown that men, often the primary earners in their families, might prioritise work over seeking medical care due to the fear of lost wages or the inability to support their families during illness.…”
Section: Discussionmentioning
confidence: 99%